2016
DOI: 10.1038/ncomms10627
|View full text |Cite
|
Sign up to set email alerts
|

Transition to a Moist Greenhouse with CO2 and solar forcing

Abstract: Water-rich planets such as Earth are expected to become eventually uninhabitable, because liquid water turns unstable at the surface as temperatures increase with solar luminosity. Whether a large increase of atmospheric concentrations of greenhouse gases such as CO2 could also destroy the habitability of water-rich planets has remained unclear. Here we show with three-dimensional aqua-planet simulations that CO2-induced forcing as readily destabilizes the climate as does solar forcing. The climate instability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 33 publications
8
85
4
Order By: Relevance
“…The LEBM lacks the vertical dimension that is necessary to represent the climate instabilities at higher temperatures. Hence, the model is neither able to produce a Runaway Greenhouse2021222324 nor cloud-induced instabilities found in this and two previous studies that lead to a transition from a habitable state to a Moist Greenhouse state1325. This explains why the transition to a hot uninhabitable state occurs so close to stars in ref.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…The LEBM lacks the vertical dimension that is necessary to represent the climate instabilities at higher temperatures. Hence, the model is neither able to produce a Runaway Greenhouse2021222324 nor cloud-induced instabilities found in this and two previous studies that lead to a transition from a habitable state to a Moist Greenhouse state1325. This explains why the transition to a hot uninhabitable state occurs so close to stars in ref.…”
Section: Resultscontrasting
confidence: 55%
“…In this work, we investigate the effect of the full three-body dynamics on the atmosphere of an Earth-like planet in a system similar to Kepler-35, by combining a state-of-the art GCM13 with an analytic orbit propagator for circumbinary planets14. The Kepler-35 binary-system consists of two stars only slightly less luminous than the sun on a mutual orbit with a semimajor axis of 0.176 a.u.…”
mentioning
confidence: 99%
“…Note that Popp et al (2016) similarly find that ECHAM is significantly more sensitive than CAM4 to increasing stellar flux from the Sun. The striking differences in climate between these simulations highlights the need for detailed model intercomparison to ascertain why the models diverge.…”
Section: Control Simulationsmentioning
confidence: 56%
“…see Fig. 7a in Popp et al, 2016). We still have much to learn both scientifically and technically, as we apply our 3-D models to the new and exotic atmospheres of extrasolar planets.…”
Section: Introductionmentioning
confidence: 99%
“…Kasting et al (1993b) found that the runaway greenhouse limit for a planet with a water reservoir of one Earth ocean does not depend on the amount of CO 2 in the atmosphere, while the water loss limit occurs at smaller orbital distances if the atmosphere contains more CO 2 . A study by Popp et al (2016) also found that the inner boundary of the HZ as determined by water loss can be strongly influenced by the CO 2 content of the atmosphere. Since we obtain a much smaller water reservoir than one Earth ocean by outgassing from the interior of a stagnant-lid planet, the atmospheres at the inner edge of the HZ are not necessarily dominated by water vapor as is the case in the runaway greenhouse scenarios as modelled by Kasting et al (1993b).…”
Section: Habitabilitymentioning
confidence: 94%